Techniques for direct experimental evaluation of structure-transport relationships in disordered porous solids - Nepryahin, Artjom; Fletcher, Robin S.; Holt, Elizabeth M.; Rigby, Sean P. (Springer, 2016)
Determining structure-transport relationships is critical to optimising the activity and selectivity performance of porous pellets acting as heterogeneous catalysts for diffusion-limited reactions. For amorphous porous systems determining the impact of particular aspects of the void space on mass transport often requires complex characterization and modelling steps to deconvolve the specific influence of the feature in question. These characterization and modelling steps often have limited accuracy and precision. It is the purpose of this work to present a case-study demonstrating the use of a more direct experimental evaluation of the impact of pore network features on mass transport. The case study evaluated the efficacy of the macropores of a bidisperse porous foam structure on improving mass transport over a purely mesoporous system. The method presented involved extending the novel integrated gas sorption and mercury porosimetry method to include uptake kinetics. Results for the new method were compared with those obtained by the alternative NMR cryodiffusometry technique, and found to lead to similar conclusions. It was found that the experimentally-determined degree of influence of the foam macropores was in line with expectations from a simple resistance model for a disconnected macropore network.